Group A streptococcal toxic shock syndrome secondary to necrotizing pelvic inflammatory disease in a postmenopausal woman. (2016) - Paulson, Qiwei; Douglass, Elizabeth; Moreno, Alejandro; Aydelotte, Jayson
Abstract: Group A β-hemolytic streptococcus (GAS) is well known to cause upper respiratory tract or cutaneous infections, but some more virulent species of GAS can lead to a rapidly progressive life threatening soft tissue necrotizing infection and streptococcal toxic shock syndrome (STSS). In the modern era, GAS infections within the female reproductive tract leading to STSS are unusual and are often the result of retained products of conception or intrauterine devices. This report describes a case of GAS necrotizing pelvic infection in a previously healthy menopausal woman with no obvious portal of entry. Her clinical course rapidly progressed to septic shock and multiorgan failure. She required multiple surgeries in addition to targeted antimicrobials and aggressive management of shock and organ failures. After a prolonged hospital stay, she had a full recovery.